Nghiên cứu tính chất vật liệu thủy tinh y sinh 45S tổng hợp từ nguyên liệu chính cát trắng - Xuân Vương, Bùi (VNU Journal of Science: Natural Sciences and Technology; Vol 33 No 2, 2017)
A bioactive glass 46S6 with composition 46% SiO 2 - 24% CaO - 24% Na 2 O - 6% P 2 O 5 (wt%) was elaborated by melting method. ‘‘In vitro’’ bioactivity of bio-glass was evaluated by soaking of glass-powders in a simulated body fluid (SBF) at different times. The obtained results highlighted the bioactivity of the bio-glass by the formation of a bioactive hydroxyapatite (HA) layer on its surface. Experiments ''in vitro'' in the presence of cells confirmed the non-toxicity and the good cell viability on this bio-glass.